2017
DOI: 10.3329/jesnr.v10i1.34688
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination in Water and Sediments of Passur River near the Sundarbans Mangrove of Bangladesh

Abstract: The study was conducted to investigate the heavy metal contamination in water, sediment and fishes from the Passur river in the Mongla port area near Sundarbans mangrove during the period from January to June 2013. The water samples were collected from five different sampling stations as St-1 (upstream-1km upper from port area), St-2 (port area), St-3 (downstream-1km lower from port area), St-4 (tributary) and St-5 (1 km lower from tributary). Sediment samples were collected monthly from Station-1, 2 and 3 dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…It was found that fishes from the Meghna River and the Paira River were both contaminated by Pb [74,77]. Fortunately, river water, sediments, and fishes from non-industrial areas like Rupsha [81,82] in Khulna, Possur [69], near the Mongla port, Bramaputra [33], near Chilmari, and Kurigram and Dakatia [83], near Chandpur, remain uncontaminated based on available reports.…”
Section: Water Heavy Metal and Metalloid Pollutionmentioning
confidence: 99%
“…It was found that fishes from the Meghna River and the Paira River were both contaminated by Pb [74,77]. Fortunately, river water, sediments, and fishes from non-industrial areas like Rupsha [81,82] in Khulna, Possur [69], near the Mongla port, Bramaputra [33], near Chilmari, and Kurigram and Dakatia [83], near Chandpur, remain uncontaminated based on available reports.…”
Section: Water Heavy Metal and Metalloid Pollutionmentioning
confidence: 99%
“…For the evaluation of upcoming pollution problems, a substantial number of industrial establishments are expected to be built at Rampal in addition to the coal-based power station. The majority of earlier research has focused on the river bed sediments in and around Rampal. , …”
Section: Introductionmentioning
confidence: 99%
“…In the Passur river in Bangladesh, showed an average Pb concentration of 6.919, with maximum values of 12.200 in June and 11.710 mg Kg -1 in May. Meanwhile, in the remaining months the concentrations of this element had the following distribution: 1.035; 1.110; 6.480; 8.980 mg Kg -1 for January, February, March, April, respectively [43]. Differences in heavy metal concentrations between seasons can be associated with variations in environmental conditions and discharges of pollutants.…”
Section: Lead Concentration (Pb)mentioning
confidence: 98%